Public Transport Accessibility Policy for Disabled Batam City in the Concept of Sustainable Transportation - Paselle, Enos; Khairina, Etika; Taufik, Mohammad; Zhan, Fuzy Firda (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
This study evaluates sustainable transportation development in Batam City, focusing on the accessibility of public transportation for persons with disabilities as a sustainability indicator. Utilizing qualitative research methods, primary data were collected through interviews, complemented by secondary data from various sources such as Department of Transportation reports, Batam City Government documents, and online media. Data analysis employed triangulation, supported by Vosviewer Tools for processing secondary data. Findings reveal inadequate transportation accessibility services for people with disabilities in Batam City. Effectiveness, efficiency, adequacy, and equality for this demographic remain suboptimal, indicating a lack of sustainable and inclusive approaches. Regional regulations concerning disabilities are not fully implemented, and there's a lack of management strategies for transportation or Transport Demand Management tailored to assist people with disabilities. The Bus Rapid Transit (BRT) system's ineffectiveness hampers transportation connectivity, exacerbating access challenges. Essential disability facilities like ramps and bell signals are unevenly provided, while the limited number of special seats creates difficulties in prioritizing pregnant women and the elderly. Consequently, the current serviceability access falls short of meeting the standard needs of people with disabilities, as envisioned in Sustainable Transportation frameworks.